Defining the Size Threshold of PEGylated Nanomedicines Crossing the Human Placenta Enables Safe Prenatal Therapies - Kensuke Suzuki; Pengwen Chen; Takuya Miyazaki; Jingyu Wan; Kazue Mizuno; Kazunori Igarashi; Keiichi Kumasawa; Yasuko Terada; Yasushi Hirota; Yutaka Osuga; Kazunori Kataoka; Takeshi Nagamatsu; et al. (ACS Nano Medicine, 2026)
Abstract Pregnant patients have limited treatment choices to ensure fetal safety as many drugs can breach the placental barrier. Nanomedicine has the potential to offer safe systemic treatments by precisely managing the drug distribution and activity. However, designing nanomedicines that avoid transport to the fetus is challenging, especially because of the differences in the placentas between species. To address this challenge, we investigated the permeability of the human placenta to various PEGylated nanoparticles, discovering a critical size threshold of 30 nm for fetal transport. Guided by this finding, we developed two types of PEGylated nanomedicines, i.e., anti-inflammatory agents for preterm birth prevention and cytotoxic treatments for cancer during pregnancy. In mouse models, these nanomedicines demonstrated therapeutic efficacy without crossing the placental barrier, ensuring fetal well-being. Our research establishes a foundation for safe and effective disease management during pregnancy via size-controlled nanomedicines, with high potential for clinical translation.